'Puppet of skeletal escapade': Dance Dialogues in Mina Loy and Carl Van Vechten. Issue 2 (May 2021) - Girdwood, Megan
Abstract : In an undated letter, likely composed in late 1914, Mina Loy reflected on the recent aesthetic experiences that had greatly affected her, writing that the 'things that have made [her] gasp were a few Picassos, Windham [ sic ] Lewis, Nijinski dancing – perfection is infrequent'. The letter was addressed to her American agent Carl Van Vechten, a dance and music critic at the New York Times, who played a highly influential role in shaping discourses around ballet and modern dance both in the US and internationally. This article conjoins Loy and Van Vechten's modernist oeuvres – crossing genres including poetry, novels, newspaper reviews, and photography – in order to reveal the importance of dance to their shifting aesthetic commitments and shared interest in the expressive capacities of the human form. Dancing bodies, moving fluently across the work of this modernist pair, variously transcribe Futurist satires, Decadent revivals, and a primitivist fascination with the erotic aspects of dance, crystallising in Loy and Van Vechten's responses to the Harlem Renaissance.